Concurrent Infection of Skunk Adenovirus-1, Listeria monocytogenes, and a Regionally Specific Clade of Canine Distemper Virus in One Gray Fox (Urocyon cinereoargenteus) and Concurrent Listeriosis and Canine Distemper in a Second Gray Fox - David B. Needle; Jacqueline L. Marr; Cooper J. Park; Cheryl P. Andam; Annabel G. Wise; Roger K. Maes; Rebecca P. Wilkes; Eman A. Anis; Inga F. Sidor; Dalen Agnew; Julie C. Ellis; Patrick Tate; et al. (Pathogens, 2020)
One free-ranging Gray fox (Urocyon cinereoargenteus) underwent autopsy following neurologic disease, with findings including morbilliviral inclusions and associated lesions in numerous tissues, adenoviral intranuclear inclusions in bronchial epithelial cells, and septic pleuropneumonia, hepatitis, splenitis, and meningoencephalitis. Molecular diagnostics on fresh lung identified a strain within a distinct clade of canine distemper that is currently unique to wildlife in New England, as well as the emerging multi-host viral pathogen skunk adenovirus-1. Bacterial culture of fresh liver resulted in a pure growth of Listeria monocytogenes, with whole genome sequencing indicating that the isolate had a vast array of antimicrobial resistance and virulence-associated genes. One year later, a second fox was euthanized for inappropriate behavior in a residential area, and diagnostic workup revealed canine distemper and septic L. monocytogenes, with the former closely related to the distemper virus found in the previous fox and the latter divergent from the L. monocytogenes from the previous fox.